Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

1) Aplica el producto notable y desarrolla:
a) [tex](x+30)^2=[/tex]
b) [tex](7x+5y)^2=[/tex]
c) [tex]\left(12a^2b^3+6a^3b^2\right)^2=[/tex]


Sagot :

Claro, vamos a aplicar el producto notable y desarrollar cada uno de los términos.

1. Parte a): [tex]\((x + 30)^2\)[/tex]

Para desarrollar [tex]\((x + 30)^2\)[/tex] usamos el binomio al cuadrado:
[tex]\[ (a + b)^2 = a^2 + 2ab + b^2. \][/tex]

Aquí [tex]\( a = x \)[/tex] y [tex]\( b = 30 \)[/tex].

[tex]\[ (x + 30)^2 = x^2 + 2 \cdot x \cdot 30 + 30^2. \][/tex]

Simplificamos cada término:
[tex]\[ x^2 + 60x + 900. \][/tex]

Por lo tanto:
[tex]\[ (x + 30)^2 = x^2 + 60x + 900. \][/tex]

2. Parte b): [tex]\((7x + 5y)^2\)[/tex]

Para desarrollar [tex]\((7x + 5y)^2\)[/tex] usamos el binomio al cuadrado:
[tex]\( (a + b)^2 = a^2 + 2ab + b^2. \)[/tex]

Aquí [tex]\( a = 7x \)[/tex] y [tex]\( b = 5y \)[/tex].

[tex]\( (7x + 5y)^2 = (7x)^2 + 2 \cdot (7x) \cdot (5y) + (5y)^2. \)[/tex]

Simplificamos cada término:
[tex]\[ 49x^2 + 70xy + 25y^2. \][/tex]

Por lo tanto:
[tex]\[ (7x + 5y)^2 = 49x^2 + 70xy + 25y^2. \][/tex]

3. Parte c): [tex]\(\left(12a^2b^3 + 6a^3b^2\right)^2\)[/tex]

Para desarrollar [tex]\(\left(12a^2b^3 + 6a^3b^2\right)^2\)[/tex] usamos de nuevo el binomio al cuadrado:
[tex]\[ (a + b)^2 = a^2 + 2ab + b^2. \][/tex]

Aquí [tex]\( a = 12a^2b^3 \)[/tex] y [tex]\( b = 6a^3b^2 \)[/tex].

[tex]\[ (12a^2b^3 + 6a^3b^2)^2 = (12a^2b^3)^2 + 2 \cdot (12a^2b^3) \cdot (6a^3b^2) + (6a^3b^2)^2. \][/tex]

Simplificamos cada término:
[tex]\[ (12a^2b^3)^2 = 144a^4b^6, \][/tex]
[tex]\[ 2 \cdot 12a^2b^3 \cdot 6a^3b^2 = 144a^5b^5, \][/tex]
[tex]\[ (6a^3b^2)^2 = 36a^6b^4. \][/tex]

Juntamos todos los términos:
[tex]\[ 144a^4b^6 + 144a^5b^5 + 36a^6b^4. \][/tex]

Por lo tanto:
\left(12a^2b^3 + 6a^3b^2\right)^2 = 36a^6b^4 + 144a^5b^5 + 144a^4b^6.

En resumen:

a) [tex]\((x + 30)^2 = x^2 + 60x + 900\)[/tex]

b) [tex]\((7x + 5y)^2 = 49x^2 + 70xy + 25y^2\)[/tex]

c) \((12a^2b^3 + 6a^3b^2)^2 = 36a^6b^4 + 144a^5b^5 + 144a^4b^6).
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.